The Effect of Regional Fiscal Capacity and Capital Expenditure on Economic Growth in Central Java Province - Susiani, Diah; Nurul Hanifa (Efficient: Indonesian Journal of Development Economics, 2026)
This study will review the outcome of the fiscal policies and capital expenditure of the region on economic growth on Central Java Province in the 2021-2024 period. In panel data regression analysis performed with EViews 12 using quantitative approach. The findings indicate that regional retribution and capital expenditure have a positive as well as significant influence to the economic growth whereas the same is not true of the regional tax. This analysis shedding light on the fact that long term economic growth is possible by making good fiscal management and a specific focus on investment by the government. In practice, the results offer some strategic information to policymakers that can improve regional financial autonomy, and efficiency of capital expenditure and inclusion and sustainability of regional development.